ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN GO PUBLIC DI BURSA EFEK INDONESIA (BEI) TAHUN 2007-2011 - SE, Winda; SE., M.Si., AK, Murtini (STIE Muhammadiyah Pekalonga, 2013)
This study aims to examine and analyze the factors which affect Â capital structure, the dependent variable is capital structure and independent variables include : profitability, firm size, asset structure, profit growth, business risk and operating leverage . The population used is a mining company listed on the Stock Exchange for 5 years (2007 s / d 2011). The method of analysis used multiple regression which preceded the classic assumption test. In conducting the hypothesis test (F test and t test) and coefficient of determination (R2) is used SPSS software version 16 .The findings of this study are variable profitability, firm size, business risk significantly influence the companys capital structure. While based on simultaneous test (F test) profitability, firm size , asset structure, profit growth, business risk and operating leverage significant effect on capital structure. The magnitude of these effects is 0.677 or 67.7 %. While the remaining 32.3 % is explained by variables or other causes outside the model.Keywords: firm size, asset structure, income growth, business risk, operating leverage and capital structure